Stable isotope analysis reveals sexual and environmental variability and individual consistency in foraging of thin-billed prions - Quillfeldt, Petra; McGill, Rona A.R.; Masello, Juan F.; Weiss, Felix; Strange, Ian J.; Brickle, Paul; Furness, Robert W.; Justus Liebig University Giessen (My University, 2008)
Based on growing knowledge on the distribution of stable isotopes in marine food webs, a powerful tool to study movements and trophic position of seabirds has been developed. Here we provide an updated review of isotope studies in the Southern Ocean and use δ13C and δ15N to evaluate diet and foraging areas of a small pelagic seabird, the thin-billed prion Pachyptila belcheri, breeding on the Falkland Islands. We found that close to egg laying, adults foraged in Falkland waters or northerly, but used more southerly foraging areas during courtship and chick rearing. Feathers grown during winter indicated that most individuals migrated south, although a small number of adults migrated north every year, consistent with regular winter observations of this species off Patagonia and southern Brazil. Thus, Antarctic waters are used regularly, but not exclusively, during the breeding and inter-breeding season. We document sex-specific segregation in foraging for the first time in this species. Males and females differed in δ13C and δ15N during courtship and chick feeding. On average, males foraged at a higher trophic level and further north than females. The isotopic signatures of blood sampled from individual chicks at different ages were correlated, indicating consistent behaviour of adult pairs over the chick-rearing period. Analysis of differences among years revealed more depleted isotope values during warmer years, suggesting more southerly foraging and a lower trophic level diet. This agrees with previous studies suggesting that warm sea surface waters depress local food availability, forcing prions to undertake longer foraging trips further south.
Keywords: Stable isotopes; Diet; Foraging area; Pachyptila belcheri; Southwest Atlantic; ddc:570; ddc:590